Nisei Radicals : The Feminist Poetics and Transformative Ministry of Mitsuye Yamada and Michael Yasutake - Fujino, Diane Carol (Book collections on Project MUSE., 2020)
"Demanding liberation, advocating for the oppressed, and organizing for justice, siblings Mitsuye Yamada (1923-) and Michael Yasutake (1920-2001) rebelled against respectability and assimilation, charting their own paths for what it means to be Nisei. Raised in Seattle and then forcibly removed and detained in the Minidoka concentration camp, their early lives mirrored those of many Japanese Americans. Yasutake's pacifism endured even with immense pressure to enlist during his confinement and the years following World War II. His faith-based activism guided him in condemning imperialism and inequality, and he worked tirelessly to free political prisoners and defend human rights. Yamada became an internationally acclaimed feminist poet and professor who continues to speak out against racism and patriarchy. Weaving together the stories of two distinct but intrinsically connected political lives, Nisei Radicals examines the siblings' half century of dedication to global movements, including multicultural feminism, Puerto Rican independence, Japanese American redress, Indigenous sovereignty, and more. From displacement and invisibility to insurgent mobilization, Yamada and Yasutake rejected the "quiet American" stereotype and fought to dismantle systems of injustice."--